COLORS AND ENVIRONMENT - Upadhyay, Padma; Mahajan, Saroj (International Journal of Research -GRANTHAALAYAH, 2014)
In last 50 years when the scientist become more aware about the environment as a whole, and started analyzing the data of water pollution, they were shocked to know that, 2% to 50% of synthetic dyes used are not utilized and go as a waste in effluents of industries. These dyes are highly soluble in water, resulting in the deterioration of COD and BOD content of the water stream, in which these effluents meet, affecting the flora and fauna of the concern region [3]. Since India is the major exporter and user of these synthetic dyes the situation is more alarming here.